Exploring Bangladeshi learner’s understanding of form, meaning and unction in L3 rench: the case of the subjunctive mood - Rahman, M (2022)
This study aimed at exploring Bangladeshi L3 French learners’ understanding of the form, meaning and function of the subjunctive in French and their ability to use them in productive skills. The study adopted an exploratory sequential mixed method research design. The quantitative data were collected through Grammaticality Judgement Task (GJT), Elicited Imitation Task (EIT), spontaneous writing task and spontaneous oral task. The GJT and spontaneous writing task were administered to check learners’ explicit knowledge of the subjunctive in French while EIT and spontaneous oral task were administered to check learner’s implicit knowledge i.e. their competence in using the subjunctive mood spontaneously and subconsciously. The data were collected from 38 tertiary level students who have been studying for a BA or an MA in French Language and Culture (FLC). A semi-structured interview was also conducted among 6 purposefully selected participants based on their performance in the GJT and EIT. The analysis of quantitative data revealed that the learners performed very well in the GJT task implying that they have developed explicit knowledge about the French subjunctive. On the other hand, they have used only a very few subjunctives both in writing and speaking tasks. The study also identified their tendency to use non-subjunctive structures in the contexts where the use of subjunctive structures could express the same meaning. The study further revealed that the participants lacked proficiency in speaking and writing in French in general.